Ressecção lateral do conduto auditivo externo: Avaliação no tratamento da otite externa crônica e proposta do uso de adesivos - Wilhelm, Graziela (2010)
The external otitis corresponds to all inflammatory process, acute or chronic, that reaching the external auditory epithelium, may also affect the pinna. In chronic or recurrent cases of canine otitis, not responsive to therapy with drugs, the surgical treatment is indicating, thus, lateral resection to external auditory canal one of the techniques applied. The objective of this work was evaluated the clinical, microbiological and histopathological aspects of the resection of the lateral external auditory canal in the treatment of chronic external otitis in dogs and compared the surgical wounds healing process of the external auditory and the lumbar region skin of rabbits using in the suture tissue adhesives and nylon yarn. In the first experiment was studying seven canines with chronic recurrent, with time course of a year or more, not responsive to drug treatment, presenting vertical conduit stenosis, ceruminous secretion (moderate to abundant) or purulent secretion and presence of erythema (moderate to intense). In the 0 day the dogs were evaluated clinically and collected samples of ear secretion for microbiological analysis and, after, submitted to lateral resection of external auditory canal procedure. In the 45, 60, 90 days postoperative, the dogs were reassessed clinically and micorbiologically as the evolution of otitis. The auditory pinna was evaluated as the purid and erythema presence. The external auditory canal was evaluated considering the presence of erythema, secretion, stenosis, tumor and growth offungi and bacteria. In the second experiment 12 rabbits was used (n=24 ears) submitted to lateral resection of external auditory canal and to two cutaneous incision in the dorsal region. The surgical wounds suture were realized with monofilament nylon and tissue adhesives. The clinical aspects of the surgical wounds healing process in the 1º, 3º, 7º, 14º and 21º postoperative day (pod) were evaluated. At the end of the experiment (21º postoperative day) were collected surgical wounds samples for hystopathology analysis. The results of the experiment with dogs demonstrated that the lateral resection technical of external auditory was effective in the chronic external otitis treatment, it shown a significant reduce (p<0,000) of the erythema, pruritus and secretion when compared the 0 day with 45, 60 and 90 postoperative day. In the experiment realized with rabbits, the surgical wounds of the ears and the skin clinical evaluations indicating no significant difference (p >0,05) between the treatments, with a tendency towards outcome in the healing process, of etyl-cyanocrylate. When compared the surgical wounds healing of the ears and the skin, was evidenced that in the skin the three treatments were greatest than in the ear. The results demonstrated that the lateral resection of the external auditory conduit was effective in the chronic external otitis treatment and that both the monofilament nylon 5-0 and the n-butyl cyanoacrylate adhesives (Vetbond®) and etyl-cyanoacrylate (Super Bonder®) were acted in similar form in the surgical wounds healing, with a tendency to better the healing evolution when using the etyl-cyanocrylate.